A numerical study of 3D topographic site effects considering wavefield incident direction and geomorphometric parameters - Wang, Fuchen; Ma, Qiang; Tao, Dongwang; Xie, Quancai (Frontiers in Earth Science, 2023)
The topographic site effect plays a vital role in controlling the characteristics of earthquake ground motions. Due to its complexity, the factors affecting topographic amplification have not been fully identified. In this study, 100 ground motion simulations generated by double-couple point sources in the homogeneous linear elastic half-space are performed based on the 3D (three-dimensional) Spectral Element Method, taking the Menyuan area of Qinghai Province, China as a local testbed site. A relationship between incident direction and the strength of topographic amplification has been observed. The horizontal ground motion is affected by the back-azimuth, which is typically chosen to be the direction from seismic station to seismic source measured clockwise from north. Specifically, the east-west PGA (Peak Ground-motion Acceleration) is significantly amplified when back-azimuth is about 90° or 270°, and the north-south PGA is significantly amplified when back-azimuth is around 0° or 180°. The vertical ground motion is affected by the dipping angle, which is the angle from vertical at which an incoming seismic wave arrives. The vertical PGA is strongly amplified when the seismic wave is almost horizontally incident (e.g., dipping angle = 78°). A correlation study between geomorphometric parameters and frequency-dependent topographic amplification indicates that relative elevation and smoothed curvature contain similar information, both of which are closely related to the topographic amplification of horizontal components, but not the vertical component. Our study reveals the influence of source and propagation path on topographic amplification and provides a reference for considering the topographic site effect in real engineering sites.